Encyclopedia of Native American tribes - Waldman, Carl, 1947- (New York : Checkmark Books, 2006)
A fully updated and revised edition of FOF's 1952 Encyclopedia of Native American Tribes, Revised Edition with 60 new entries, covers more than 200 American Indian tribes of North America. Includes 259 color illustrations (12 new to this edition), 11 color maps, cross-references, a glossary, a bibliography, and an index.
Includes bibliographical references (p. 345-349) and index.
Keywords: Indians of North America -- Encyclopedias, Juvenile